Effects of Portulaca oleracea (purslane) on liver function tests, metabolic profile, oxidative stress and inflammatory biomarkers in patients with non-alcoholic fatty liver disease: a randomized, double-blind clinical trial - Milkarizi, Narges; Barghchi, Hanieh; Belyani, Saba; Bahari, Hossein; Rajabzade, Farnood; Ostad, Andisheh Norouzian; Goshayeshi, Ladan; Nematy, Mohsen; Askari, Vahid Reza (Frontiers in Nutrition, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) is a prevalent chronic liver disease.Portulaca oleracea exhibits anti-oxidant, anti-inflammatory, and hepatoprotective effects. This clinical trial aimed to investigate the potential benefits of Portulaca oleracea in improving NAFLD.Methods: This double-blind, randomized clinical trial enrolled 70 patients with NAFLD assigned to either the intervention group (n=35) or placebo group (n=35) using stratified block randomization. The intervention group received 700 mg Portulaca oleracea supplement for eight weeks, while the control group received placebo capsules. In addition, all participants received a calorie-restricted diet. Liver steatosis and fibrosis were assessed using elastography along with liver function and metabolic tests, blood pressure measurements, body composition analysis and dietary records pre-and post-intervention.The average age of the participants was 44.01 ± 8.6 years, of which 34 (48.6%) were women. The group receiving Portulaca oleracea showed significant weight changes, body mass index, fat mass index, and waist circumference compared to the placebo (P<0.001). In addition, blood sugar, lipid profile, liver enzymes aspartate and alanine transaminase, gamma-glutamyl transferase, and systolic blood pressure were significantly improved in the intervention group compared to those in the placebo (P<0.05). During the study, inflammatory and oxidative stress indicators, improved significantly (P<0.05). Based on the elastography results, the hepatorenal ultrasound index and liver stiffness decreased significantly in the Portulaca oleracea group compared to the placebo (P<0.001).The present clinical trial showed that receiving Portulaca oleracea supplement for eight weeks can improve the condition of liver steatosis and fibrosis in patients with NAFLD.